Shift work, confounding and death from ischaemic heart disease. Issue 3 (3rd May 2007) - Yadegarfar, G; McNamee, R
Abstract : Objective: To investigate the relation between shift work and death from ischaemic heart disease (IHD) and evidence for confounding by social class and healthy shift worker effects. Methods: A case-referent study nested within an industrial cohort was used. Cases (n = 635) were cohort members who died of ischaemic heart disease (ICD 410–414) during 1950–98 aged 75 or under. Referents were matched on age and year of starting work at the site and were alive at time of case's death. Shift work status was determined from historical personnel records and pre-employment weight, height, blood pressure and smoking from medical records. Social class at first employment was inferred from job titles. To overcome potential bias due to a healthy shift worker hire effect, odds ratios were calculated from survivors 10 years after hire. To control for any healthy shift worker survivor effect, they were adjusted for duration of employment and time since termination of employment. Conditional logistic regression analysis was used to estimate ORs. Results: 55% of subjects had worked as shift workers. Shift workers were more likely than day workers to belong to social class IV or V. The OR for shift workers compared with day workers, after adjustment for pre-employment risk factors, duration of employment and restricted to those who survived 10 years after hire was 1.11 (90% CI 0.90 to 1.37). This reduced to 1.04 (90% CI 0.83 to 1.30) after inclusion of social class. No dose-response relation was found. Conclusion: No excess risk of death from IHD for shift workers was found. The potential for confounding by social class in this relatively homogeneous cohort underlines the need to consider such confounding in more heterogeneous populations.